Depression and Identity: Are Self-Constructions Negative or Conflictual? - Montesano, Adrián; Feixas, Guillem; Caspar, Franz; Winter, David (Frontiers in Psychology, 2017)
Negative self-views have proved to be a consistent marker of vulnerability for depression. However, recent research has shown that a particular kind of cognitive conflict, implicative dilemma, is highly prevalent in depression. In this study the relevance of these conflicts is assessed as compared to the cognitive model of depression of a negative view of the self. In so doing, 161 patients with major depression and 110 controls were assessed to explore negative self-construing (self-ideal discrepancy) and conflicts (implicative dilemmas), as well as severity of symptoms. Results showed specificity for the clinical group indicating a pattern of mixed positive and negative self-descriptions with a high rate of conflict. Regression analysis lent support to the conflict hypothesis in relation to clinically relevant indicators such as symptom severity, global functioning. However, self-ideal discrepancy was a stronger predictor of group membership. The findings showed the relevance of cognitive conflicts to compliment the well-consolidated theory of negative self-views. Clinical implications for designing interventions are discussed.